Synthesis, characterization and some properties of novel bis(pentafluorophenyl)methoxyl substituted metal free and metallophthalocyanines - ÖZKAYA, ALİ RIZA; ÖZER, METİN (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
The preparation of some new tetrakis[bis(pentafluorophenyl)methoxyl] substituted metal free and metalloplithalocyanine (MPcs) complexes were achieved by the tetramerization of 4-[bis(pentafluorophenyl)methoxy]phthalonitrile with Li metal in pentan-1-ol or metal [Co(II) or Zn(II)] acetates in DMAE, respectively. The structures of the target compounds were confirmed by elemental analysis, IR, UV-vis, H-1 NNIR, F-19 NMR and mass spectroscopic methods. MPcs are soluble only in strong and medium polar solvents while the metal free one is soluble in weakly, medium and strong polar solvents. The temperature and frequency dependence of the electrical conductivities were studied on spin coated films of the compounds using dc and impedance spectroscopy techniques in the frequency range from 40 to 10(5) Hz and within the temperature range from 290 to 440 K. The temperature dependence of the exponent s and conductivity, sigma(ac), were completely in agreement with the prediction of the hopping model. The redox properties of the complexes were determined by cyclic voltammetry. The nature of the redox processes was also confirmed using spectroelectrochemcal measurements. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: phthalocyanine; synthesis; bis(pentafluorophenyl)methoxyl; UV vis spectra; cyclic voltammetry; spectroelectrochemistry; impedance spectra; PHTHALOCYANINE; MANGANESE; COBALT